Hubungan antara motivasi belajar dengan prestasi belajar mahasiswa - Yuriatson Yuriatson; A.Syamsinar Asmi (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background; improving the quality of human resources is a must for the world, especially in the era of globalization which demands the readiness of every nation to compete freely. Method; Analytical descriptive with a cross sectional study design where the researcher made observations or instantaneous variable measurements, meaning that the subject was observed only once and explored simultaneously using a questionnaire measuring instrument. Through population determination, sampling and sampling, data collection, data processing and data analysis. Result; The analysis shows that 28 respondents (84.8%) have good motivation, 1 respondent (3.0%) is moderate, and there is no lack of achievement. Meanwhile, 4 respondents (12.1%) had less motivation to learn. Conclusion; motivation has an important function in learning, because motivation will determine the intensity of the student's learning efforts